Using Ventilator-Associated Pneumonia Rates as a Health Care Quality Indicator: A Contentious Concept - Nair, Girish B.; Niederman, Michael S. (Seminars in Respiratory and Critical Care Medicine, 2017)
Pneumonia is a leading cause of hospital-acquired infections, although reported rates of ventilator-associated pneumonia (VAP) have been declining in recent years. A multifaceted infection prevention approach, using a “ventilator bundle,” has been shown to reduce the frequency of VAP, while improving other patient outcomes. Because of difficulties in defining VAP, the Center for Medicare and Medicaid Service introduced a new streamlined ventilator-associated event (VAE) definition in 2013 for the surveillance of complications in mechanically ventilated patients. VAE measures are increasingly being measured by institutions in the United States in place of VAP rates and as a potential measure of the quality of intensive care unit (ICU) care. However, there is increased recognition that the streamlined definitions identify a different subset of patients than those identified by traditional VAP surveillance and that VAP prevention strategies may not impact all the causes of VAE. Also, VAP and VAE rates may not always reflect the quality of care in a given ICU, especially since patient factors, beyond the control of the hospital, may impact the rates of VAP and VAE. In this review, we discuss the issues related to VAP as a quality measure and the areas of uncertainty related to the new VAE definitions.
Keywords: nosocomial pneumonia; ventilator-associated pneumonia; ventilator-associated events; ventilator-associated complications; prevention; quality measure